2004
DOI: 10.2214/ajr.183.4.1830975
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study Comparing Sonographic and MRI Assessments of Acute and Healing Hamstring Injuries

Abstract: Sonography is as useful as MRI in depicting acute hamstring injuries and because of lower costs may be the preferred imaging technique. However, MRI is more sensitive for follow-up imaging of healing injuries. The longitudinal length of the strain as measured on MRI is a strong predictor for the amount of time needed until an athlete can return to competition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
472
2
16

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 411 publications
(520 citation statements)
references
References 18 publications
18
472
2
16
Order By: Relevance
“…Among them, a prospective study 14 showed that sonography was as useful as MRI for assessing acute hamstring injury (48 injuries in our study).…”
Section: Discussionmentioning
confidence: 69%
“…Among them, a prospective study 14 showed that sonography was as useful as MRI for assessing acute hamstring injury (48 injuries in our study).…”
Section: Discussionmentioning
confidence: 69%
“…Whereas musculoskeletal ultrasound has been demonstrated to be an effective tool for assessing acute HSIs, no evidence is available to support its use in making RTP decisions. 75 Although the ATs did not place a high level of importance on bilateral isokinetic testing, it is an RTP component of clinical commentaries, and most of the available evidence supports its use. Some researchers have demonstrated bilateral deficits (peak torque, angle of peak torque) in participants with previous HSIs or have shown increased risk for future reinjury due to bilateral asymmetries 55,76,77 ; however, some investigators have refuted these findings.…”
Section: Importance Of Rtp Methodsmentioning
confidence: 99%
“…In the event edema and hemorrhage occur in the injured area, these two imaging methods make it possible to make a diagnosis [24]. Magnetic resonance imaging is considered preferable when damage is found inside the muscle tissue, or for example, when mild local edema exists or when an old scar is present as a result of a previous injury [12,13,25].…”
Section: Diagnostic Imaging Methodsmentioning
confidence: 99%